Locus of control: Upaya untuk menurunkan social loafing - Sumantri, M. Arief; Pratiwi, Iqlima (University of Muhammadiyah Malang, 2020)
Objectives: Social loafing is a phenomenon of decreased performance (efforts / efforts) of individuals in the work of group-based tasks, which of course will have an impact on performance and group satisfaction. This study aimed to determine the effect of locus of control, both internally and externally on social loafing in group task completion.Method: This study uses a quantitative approach. Sampling using non-probability sampling with accidental sampling technique in the population of students majoring in education (prospective teachers), with a total number of participants as many as 147 students (45 tryout scale, 102 hypothesis testing). The measurement of each variable modifies the scale construct of previous research, which refers to Levenson for locus of control and Latane for social loafing. Then analyzed using a linear regression test.Findings: Internal locus of control in this study proved to be able to reduce social loafing (sig. 0,000), with R Square value (influence contribution) in the determination coefficient table of 0.211 or 21.1%, while external locus of control did not contribute to the effect at all.Conclusions: Internal locus of control is proven to reduce the tendency of social loafing in students, while external locus of control does not contribute to the influence at all, it does not even correlate with social loafing.